2023
DOI: 10.1002/ps.7810
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of fosmidomycin analogs containing aza‐linkers and their biological activity evaluation

Xin Wu,
Mengwei Bu,
Zili Yang
et al.

Abstract: BackgroundThe enzymes involved in the MEP pathway are attractive targets of new mode of action for developing anti‐infective drugs and herbicides, and the inhibitors against IspC, the second key enzyme in the pathway, have been intensively investigated, however, few works are reported regarding the IspC inhibitors designed for new herbicide discovery.ResultsA series of fosmidomycin (FOS) analogs with nitrogen‐containing linkers replacing the trimethylene linker between the two active substructures of FOS, phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…To validate the possible mode of action of the active compounds in this work, a DMAPP rescue assay was conducted by treating Arabidopsis with the compound pair 8m/15m and the control FOS, with the supplement of DMAPP, the product of the MEP pathway, according to a reported procedure. 28 The underlying logic of DMAPP rescue is that if the Arabidopsis growth inhibition is caused by inhibition of the DXR enzyme, adding exogenous DMAPP as a downstream product of the MEP pathway should restore the growth of Arabidopsis. As shown in Figure 5A, the bleaching and growth inhibition of Arabidopsis by 8m were effectively rescued by DMAPP, just as what happens in the case with FOS treatment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To validate the possible mode of action of the active compounds in this work, a DMAPP rescue assay was conducted by treating Arabidopsis with the compound pair 8m/15m and the control FOS, with the supplement of DMAPP, the product of the MEP pathway, according to a reported procedure. 28 The underlying logic of DMAPP rescue is that if the Arabidopsis growth inhibition is caused by inhibition of the DXR enzyme, adding exogenous DMAPP as a downstream product of the MEP pathway should restore the growth of Arabidopsis. As shown in Figure 5A, the bleaching and growth inhibition of Arabidopsis by 8m were effectively rescued by DMAPP, just as what happens in the case with FOS treatment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…On the other hand, FOS as a herbicide-active compound was tested on Arabidopsis thaliana ( Arabidopsis ) two decades ago, demonstrating the effects of bleaching and developmental arrest of wild-type Arabidopsis seedlings through inhibiting DXR. , However, their analogues for herbicide development are rarely reported. In recent years, our group reported that several aza-linker-containing FOS analogues have promising herbicidal activities and may act through targeting the DXR enzyme . These early studies provide an avenue to finding FOS analogues as novel herbicides with a new mode of action.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second enzyme in this pathway, 1-deoxy-D-xylulose 5-phosphate reductoisomerase, shortly named DXR and also known as IspC, which catalyzes the isomerization and reduction of 1-deoxy-D-xylulose 5-phosphate (DXP) to produce MEP [6], is the most encouraging target for the development of novel antibacterial and antimalarial drugs because two naturally occurring products, fosmidomycin (FOS) and FR900098 (FR), have been found active in targeting this enzyme, and the inhibition mechanism has been well documented [7,8]. Although DXR has been considered a promising target for herbicides [9,10], the research focusing on the herbicide discovery based on DXR is rather limited, making the development of DXR inhibitors as herbicidal lead compounds a work of great significance. The two natural products, FOS and FR, originally isolated from Streptomyces species [11,12], are structurally composed of three parts, namely phosphonic acid, hydroxamate and the trimethylene linker, as shown in Figure 2A.…”
Section: Introductionmentioning
confidence: 99%